Yes! No - Byrnes, Kellie; Petruso, Gabriella (Armidale, NSW : Little Pink Dog Books, 2021)
"Yes! No. is a fun graphic story for animal lovers. Using just 19 words in total ('Yes' and 'No' repeated), it tells an action-packed tale about an enterprising raccoon's efforts to steal freshly baked pie from a home, and the highs and lows which follow as it alternates between winning and losing, and then being thwarted by the home's domestic pets and small human." -- Publisher's website.
For children.
Keywords: Animals -- Pictorial works -- Juvenile fiction; Raccoons -- Pictorial works -- Juvenile fiction; Australian; Picture books; Humorous fiction